2017
DOI: 10.1103/physreve.95.042405
|View full text |Cite
|
Sign up to set email alerts
|

Stable swarming using adaptive long-range interactions

Abstract: Sensory mechanisms in biology, from cells to humans, have the property of adaptivity, whereby the response produced by the sensor is adapted to the overall amplitude of the signal; reducing the sensitivity in the presence of strong stimulus, while increasing it when it is weak. This property is inherently energy consuming and a manifestation of the non-equilibrium nature of living organisms. We explore here how adaptivity affects the effective forces that organisms feel due to others in the context of a unifor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Adaptivity is a common feature of biological sensory systems. Gorbonos & Gov [ 17 ] showed that adaptivity also prevents collapse of the swarm and therefore confers on the swarm a natural stability mechanism. This is related to Jeans instability, which in stellar physics causes the collapse of interstellar gas clouds and hence star formation when the internal gas pressure cannot prevent gravitational implosion.…”
Section: Methodsmentioning
confidence: 99%
“…Adaptivity is a common feature of biological sensory systems. Gorbonos & Gov [ 17 ] showed that adaptivity also prevents collapse of the swarm and therefore confers on the swarm a natural stability mechanism. This is related to Jeans instability, which in stellar physics causes the collapse of interstellar gas clouds and hence star formation when the internal gas pressure cannot prevent gravitational implosion.…”
Section: Methodsmentioning
confidence: 99%
“…It is crucial to bring model predictions in line with observations [4]. By preventing collapse (Jeans instability) it also endows swarms with a natural mechanism for self-stabilization [10]. Here, ‘adaptation’ arises freely and is not imposed on the model.…”
Section: Emergence Of Gravitational-like Interactions At the Macroscomentioning
confidence: 99%
“…More recent studies have uncovered more striking analogies with self-gravitating systems: including the occurrence of polytropic distributions (which constitute the simplest, physically plausible models for self-gravitating stellar systems), together with biological correlates of Jean's instabilities, black hole entropies, Mach's Principle, surface pressures, and dark matter (see refs. [10,[12][13][14]31] and Electronic Supplementary Material). By providing a revision to Okubo [1] I have uncovered another biological correlate of self-gravitating systems: namely dark energy.…”
Section: Discussionmentioning
confidence: 99%